ANALISIS KEMENANGAN HARYANTO-BUDIYONO DALAM PEMILUKADA KABUPATEN PATI - Zuqna Kartika; Muhammad Adnan; Nunik Retno H (Journal of Politic and Government Studies, 2013)
Election of regional heads Pati Regency were implemented in 2011 won by Haryanto-Budiyono. However, due to the aquisition of his voice has not reached more than 30% (thirty percent), the election go to second round selection. But there’s objection of Imam Suroso-Sudjoko. The Constitutional Court then canceled the Komisi Pemilihan Umum of Pati Regency Decission on Establishment Candidate Regent and Vice Regent, and ordered to repeat the Election. Although they return to compete with 5 other pairs of candidates, Haryanto- Budiyono earned victory back 38.85% of the vote. This is quite interesting because the Haryanto-Budiyono carried by small parties able to beat the Candidates carried by PDI-P. In fact, for 10 years Pati Regency is a bastion of PDI-P.The research method used in this study is a qualitative method. The data in this study come from interviews with respondents and obtained from the reports, books, journals, magazines, and so on. The data was then compiled with the stages of examining the data obtained from the field, analyzing the data and information and then draw conclusions and verification. Thus generating descriptive data to portray the results of the Haryanto-Budiyono winning analysis in the election of regional heads in Pati Regency.Based on the research conducted, Haryanto-Budiyono victory influenced by the Hary-anto-Budiyono figure considered competent and qualified in the bureaucracy; this couple is also superior in terms of political marketing; the succes of campaign team in developing and running a winning strategy to build an effective and efficient performance; political parties as a vehicle for political role in the recruitment of the masses and density coalition into the power of this couple.This victory also analyzed the voting behavior with the sociological approach from Haryanto-Budiyono a mass base of religious equality, the civil servants, Juwana community loyalty, sociological bond between Haryanto with community leaders; psychological victory this couple was able to demonstrate its proximity to the community; seen from the approach rational choice, people choose not because of money politics but because of the programs of-fered by this couple.Keywords : Winning Analysis In The Election Of Regional Heads, Political Marketing, Voting Behavior